Clinical characteristics and outcomes of witnessed hypothermic cardiac arrest: A systematic review on rescue collapse. (April 2019) - Frei, C.; Darocha, T.; Debaty, G.; Dami, F.; Blancher, M.; Carron, P.N.; Oddo, M.; Pasquier, M.
Abstract: Aims: Cardiac arrest related to accidental hypothermia may occur at temperatures below 32 °C. Our goal was to describe the clinical characteristics and outcomes of patients who suffered from witnessed hypothermic cardiac arrest (CA) and assess the occurrence of hypothermic CA as a function of patient body temperature. Methods: We conducted a systematic review of the literature on cases of hypothermic CA due to rescue collapse. Patient information data from hypothermic CA patients were collected and combined with additional unpublished data to assess the clinical characteristics and outcome of hypothermic CA patients. Results: A total of 214 patients was included in this systematic review. Of the 206 witnessed hypothermic CA patients with a recorded body temperature, the average body temperature was 23.9 ± 2.7 °C with five patients (2.4%) having a core body temperature of >28 °C. The highest temperature of a patient surviving hypothermic witnessed cardiac arrest without other associated risk factors for cardiac arrest was 29.4 °C. The first recorded cardiac rhythm was asystole in 33 of the 112 patients (30%) for whom this information was available. The survival rate at hospital discharge of these hypothermic cardiac arrest patients was 73% (153 of 210 patients) and most survivors had favourable neurological outcome (89%; 102 of 105 patients). Conclusions: CA that is solely caused by hypothermia did not occurs for patients with a body temperature >30 °C. Our findings provide valuable new information that can be incorporated into the international clinical management guidelines of accidental hypothermia.